‘On Psilorhynchus sucatio and P. nudithoracicus’, the sequel: Unnecessary and unscientific names lead to rapid synonymization and taxonomic time wasting—A response to Arunachalam et al. (2018) - Conway, Kevin W. (Zootaxa, 2018)
The Torrent minnows Psilorhynchus sucatio (Hamilton, 1822) and P. nudithoracicus Tilak & Husain, 1980 are widespread throughout the Ganges-Brahmaputra drainage of India, Bangladesh and Nepal (Conway et al., 2013). Like many widespread species, P. sucatio and P. nudithoracicus exhibit high levels of variation in morphological traits (particularly colour pattern) across their respective ranges and both have been described on more than one occasion by different authors examining material obtained from different parts of their range and/or unaware of earlier works. The distinctive, long-snouted torrent minnow Psilorhynchus sucatio was described by Hamilton (1822: 347) based on material from “Northern Bengal” (no types known). David (1953) introduced the name P. sucatio damodarai for a “variety” (=subspecies; ICZN, 1999; art. 45.6.4) of P. sucatio from the Damodar River (Jharkhand and West Bengal) and Tilak & Husain (1980) described the subspecies P. sucatio nudithoracicus based on material from Uttar Pradesh. In 1983, Rainboth described Psilorhynchus gracilis based on a smaller, more slender series of Psilorhynchus with a shorter snout than P. sucatio, collected in the tributaries of the Ganges and Brahmaptura rivers in northern Bangladesh. In 2013, Conway et al. argued that the names P. s. nudithoracicus and P. gracilis referred to the same species, placed the latter in the synonymy of the former, and elevated P. nudithoracicus to species status. As part of their redescription of P. sucatio and P. nudithoracicus, Conway et al. (2013) examined large series of specimens representing a range of body sizes (462 specimens of P. sucatio [13–67 mm SL] and 97 of P. nudithoracicus = [10–68 mm SL]), and encompassing almost the entire range of both species, provided multiple figures illustrating the important anatomical features of both species and, most importantly, provided clear diagnoses.